MODEL MATEMATIKA MENGENAI KESADARAN MASYARAKAT DALAM PERILAKU HIDUP BERSIH DAN SEHAT DI KOTA SAMARINDA - Pancahayani, Sigit; Arti, Rissa Putri; Fitria, Irma; Subchan, Subchan (Majalah Ilmiah Matematika dan Statistika, 2020)
Samarinda is one of the big city in Kalimantan since it is a capital city of East Kalimantan Province. Its population is about 988,943 in 2015, but only 28.62 percent of the whole households were applying clean and healthy living behavior. To encourage this behavior to the society, it needs some health promotions to be introduced to them. In order to know the pattern of clean and healthy behaving households with respect to time, so this research is aimed to perform a mathematical model of the implementation of clean and healthy living behavior which involves health promotion. Runge-Kutta is the used model to solve this model. The result informs that the rate of change of the households which implement a clean and healthy life, called as good people, increases for all sub-districts in Samarinda City. In contrast, households that do not know and do not behave clean and healthy life, called as bad people, are reduced because of the promotion. Keywords: clean and healthy living behavior, health promotion, modeling mathematics.